2011
DOI: 10.1111/j.1365-2133.2011.10551.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mutational analysis of CDKN2A and CDK4 in Greek patients with cutaneous melanoma

Abstract: Background The penetrance of CDKN2A mutations is subject to geographic and latitudinal variation and is presumably dictated by UVR exposure and possibly other co-inherited genetic factors. The frequency of mutations increases with the number of family members affected and the number of primary tumors and also fluctuates with geography. Up to date, little is known about the prevalence of CDKN2A mutations in melanoma patients from Greece. Objective To characterize the frequency of CDKN2A and CDK4 mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…22 Similarly, in a study of Greek families, Nikolaou et al reported that 22% of familial melanoma cases and 57% of individuals with multiple primary melanomas carried a CDKN2A mutation. 23 When melanoma cases were ascertained independent of family history, there was a much lower rate of mutation. The frequency of CDKN2A mutations in patients with a single primary melanoma or multiple primary melanomas were 1.2% and 2.9%, respectively.…”
Section: 2b the Genetics Of Fammmmentioning
confidence: 99%
“…22 Similarly, in a study of Greek families, Nikolaou et al reported that 22% of familial melanoma cases and 57% of individuals with multiple primary melanomas carried a CDKN2A mutation. 23 When melanoma cases were ascertained independent of family history, there was a much lower rate of mutation. The frequency of CDKN2A mutations in patients with a single primary melanoma or multiple primary melanomas were 1.2% and 2.9%, respectively.…”
Section: 2b the Genetics Of Fammmmentioning
confidence: 99%
“…In addition to PTEN alterations, mutations of CDKN2A, as well as NRAS mutations have been frequently observed in melanoma [102,103]. CDKN2A is the most often mutated tumor suppressor gene in melanoma, with 60% homozygous deletions and additional 15-20% point mutations [104][105][106].…”
Section: Pten Mutations and Other Genesmentioning
confidence: 99%
“…The prevalence of CDKN2A mutations is higher among the Greek population (which has a relatively low baseline risk of melanoma) compared to other reported cohorts, suggesting the strength of genetic factors in melanomagenesis (Nikolaou et al 2011 The cyclin-dependent kinase 4 (CDK4) gene locus encodes an enzyme that is inhibited by binding of p16 and is also found to be mutated among clusters of melanoma families (Zuo et al 1996), although CDK4 mutations are more rare than CDKN2A gene mutations. A study of 17 known families with CDK4 germline mutations showed that there are no phenotypically distinguishing features from CDKN2A families (Puntervoll et al 2013).…”
Section: Melanoma Phenotypes With Known Genetic Associations Loci Assmentioning
confidence: 87%